Employee's past environmental related experience and green supply chain management practice: A study of Malaysian chemical related industries - Jaaffar A.H.; Kaman Z.K.; Razali N.H.A.; Azmi N.; Yahya N.A. (American Institute of Physics Inc., 2023)
Little empirical work has been done on the effects of employee's past environmental related experience and firm's green supply chain management (GSCM) practice. The literature of GSCM practice suggests employee's expectation increasingly concern firm supply chains. This study aims to examine the relationship between employee's past environmental experience and GSCM practice including proactive and reactive practice. Grounded by natural resource-based view, this study utilised a research model examining the relationship between employees' past environmental related experiences (e.g. past tertiary education involved environmentally-related fields or disciplines; work experience in environmental related roles; received any award or honour related to environmental sustainability practices; and past or current membership or management role in local community events, foundations and institution such as NGO) and proactive and reactive GSCM practice among employee's in Malaysian chemical related industries. Questionnaires were distributed through postal survey to manufacturing plant employees from eight chemical manufacturing industries from four regions in Malaysia including northern, central, east-coast, and southern. A total of 202 employees participated in the study. The data collected were analysed using partial least squares structural equation modelling. Based on the analysis, the study revealed that employee's past environmental experience have positive significant relationship with GSCM practice where proactive GSCM practice have the stronger effect than reactive GSCM practice. This study extends previous research by highlighting the importance of employee with past environmental related experience in driving firm's behaviour in GSCM practice. Doing so, it reinforces the recent conceptual definition that firms should align and leverage on employees' past environmental related experience for GSCM practice effectiveness. 2019 Author(s).